Study of the Digitalization of Population Administration Services Using Population Data in Medan City Regional Development Planning - Admar, Adisti Maritadinda; Sirojuzilam, Sirojuzilam; Badaruddin, Badaruddin; Rujiman, Rujiman (International Conference on Sciences Development and Technology, 2023)
The continuation of the digitalization of population administration services towards regional development planning through the population utilization system is expected to become a common foundation to overcome various barriers in the effort to optimize data utilization. To improve this in the future, this gap becomes the subject of research. This research studies many aspects, such as recording and documentation, data publication, data development, data utilization, ease of use, quality of data information, and credibility of data administration. We also strive to enhance respondents' understanding of the population information system, what users need for data, and which data can collaborate across agencies. To accelerate the performance of regional development in addressing urgent and long-term issues, easily accessible and valid population data are required. If the data used in planning is not valid, planning that can respond to changes in social conditions becomes difficult. The validity of data referred to not only indicates whether the recorded population events match the actual conditions but also whether the recorded data can depict the actual numbers. Currently, an improved quality of planning is expected to be produced from the ease of data access for users to utilize in their field of work. As the executing agency handling population administration in Medan City, the Medan City Population and Civil Registration Office has initiated the process of developing a digital population data system. Strategies for optimizing performance continue to be implemented, and this research is expected to encourage population administration managers to support the blessed, progressive, and conducive vision and mission of Medan City.